ALKBH5 induces macrophage activation to promote renal fibrosis via Retnla - Long Zheng; Wenjun Gao; Zhenan Zhang; An He; Qi Huangfu; Jinyu Luo; Ming Wang; Juntao Chen; Ming Cai (Renal Failure)
Renal fibrosis is a common pathological endpoint of various chronic kidney diseases. Macrophages play an important role in the pathophysiological process of renal fibrosis. However, the exact function and molecular mechanism of macrophages during renal fibrosis remain unclear. In this study, we found an increased expression of RNA demethylase AlkB Homolog 5 (ALKBH5) in macrophages from the mice with unilateral ureteral obstruction (UUO) and TGF-β treatments bone marrow-derived macrophages. Macrophage-specific ALKBH5 knockout could significantly alleviate renal fibrosis in UUO mice and decrease the infiltration of macrophages in the kidneys. Further studies showed that ALKBH5 deficiency reduced M2a macrophage polarization and the expression of TGF-β1, Arg1, and CD206 both in vivo and in vitro. RNA sequencing indicated that Resistin-like alpha (Retnla) was the downstream target of ALKBH5, and treatment with recombinant Retnla abrogated the effect of ALKBH5 deficiency on renal fibrosis. We conclude that ALKBH5-dependent regulation of macrophage and kidney fibrosis progression through Retnla represents a novel strategy for patients with chronic kidney disease.